Prismatomeris fragrans E.T. Geddes (Rubiaceae) - a new record for the flora of Viet Nam (Bangladesh Journal of Plant Taxonomy, 2015)
Not available.Bangladesh J. Plant Taxon. 22(2): 147-149, 2015 (December)